To stay alive : Mary Ann Graves and the tragic journey of the Donner Party - Brown, Skila (Candlewick Press, 2018)
Traveling west by wagon train with her family, nineteen-year-old Mary Ann Graves is hopeful for her family's new life in California. But when her family is trapped in early snowstorms alongside the Donner and Reed families in Nevada, she learns the true meaning of perseverance.